Library Facebook practices for creating and promoting a professional profile. Issue 3 (6th July 2015) - Vassilakaki, Evgenia; Garoufallou, Emmanouel
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to provide an in-depth insight on librarians' use of the social networking site Facebook as a way to connect and promote interaction with library users. A series of common practices for building and maintaining a Facebook page for information professionals are thoroughly and critically presented. Design/methodology/approach – Two methods were employed for the purposes of this study. Specifically, a systematic review was adopted to identify all the relevant literature concerning librarian's use of Facebook, and a content analysis of the literature to identify the specific Facebook features used, the way these were employed by librarians, and the reasons these specific features were chosen. Findings – In total, 12 Facebook features used by librarians in the literature were identified through content analysis. The creation of the librarian's Facebook Profile was the most important featured employed followed by Groups Messages, Wall Posts, Events and Friends. Research limitations/implications – This study extents a literature review paper (Vassilakaki and Garoufallou, 2014). Therefore, only papers published between 2005 and 2012 and assigned to categories "librarians creating profiles on Facebook", "Librarians personal experiences on Facebook" and "exploring librarians' perspectives" were considered with the view to focus on librarians' views and the way they use Facebook to connect with users. Originality/value – This study contributes in providing the baseline for creating a series of best practices for librarians use of Facebook for professional purposes. Furthermore, it provides a valuable insight on the specific ways information professionals use Facebook successfully.